EVALUATION OF THE PREVALENCE OF INFECTION BY ATYPICAL GERMS IN PATIENTS WITH COMMUNITY ACQUIRED PNEUMONIA IN A PERUVIAN REFERENCE HOSPITAL: EVALUACIÓN DE LA PREVALENCIA DE INFECCIÓN POR GÉRMENES ATÍPICOS EN PACIENTES CON NEUMONÍA ADQUIRIDA EN LA COMUNIDAD EN UN HOSPITAL DE REFERENCIA PERUANO - Soto, Alonso (2019)
Objective: To determine the prevalence of infection due to atypical microorganisms in cases of communityacquired pneumonia in adult inmunocompetent patients seeking attention in the Hospital Nacional Hipolito Unanue. Methods: Adult inmunocompetent patients seeking medical attention in the emergency ward of Hospital Hipolito Unanue with diagnosis of community-acquired pneumonia were evaluated between september 2008 and january 2009. Blood samples were drawn for Mycoplasma pneumoniae and Chlamydia pneumoniae serology, by the detection of M Inmunoglobulin by ELISA technique. Results: We recruited 85 patients. The average age was 65.33 ± 21.43 years. We found 3 cases with positive IgM serology against M. pneumoniae and 1 case positive against C. pneumoniae. The antibody titers against M. pneumoniae had a highly significant correlation with the age (r=-0.28; p<0.01). We also found a statistically significant difference between the titers of antibodies against M. pneumoniae and those correspondent to C. pneumoniae (r=0.29; p<0.01). Conclusion: Infection due to atypical microorganisms doesn’t seem to be a frequent condition in inpatients with diagnosis of community-acquired pneumonia. Research in larger populations, including outpatients should be done, in order to define the role of atypical pathogens in cases of pneumonia at a national level.